Measuring Spatial Separation Processes through the Minimum Commute: the Case of Flanders - Boussauw, Kobe; Derudder, Ben; Witlox, Frank (European Journal of Transport and Infrastructure Research, 2011)
The average distance covered by individual commuting trips increases year after year, regardless of the travel mode. The causes of this phenomenon are diverse. Although increasing prosperity is often invoked as the main reason, the discipline of spatial planning also points to the relevance of land-use policies that enable processes of suburbanization and sprawl. By calculating time series of spatially disaggregated theoretical minimum commuting distances, this paper offers a method to identify and quantify the process of spatial separation between the housing market and the job market. We identify the detected spatial separation as one of the possible indicators for the contribution of spatial processes to the growth of traffic. In the case study area of Flanders and Brussels (Belgium), it is found that over time the minimum commuting distance increased in many municipalities, especially where population is growing faster than job supply, or where traditionally high concentrations of employment still increase. Decreases are noticed in suburban areas that are getting a more urban character by acquiring a considerable functional mix. For the study area in its entirety, we do indeed register an increasing spatial separation between home and work locations. However, this separation evolves less rapidly than the increase in commuting distances itself. Regarding the methodology, we find that the use of municipalities as a spatial entity is suitable for grasping regional transformations of the economy and intermunicipal forms of suburbanization and peri-urbanization. However, a similar methodology, applied at a more detailed geographical scale, could be used to detect processes of sprawl in the morphological sense.